The Effects of High Fat Diets on Body Weight and Lipid Profile Changes of Sprague-Dawley Rats - Nasution, Lailan Safina; Mustika, Aulia Andi; Andriyanto, Andriyanto (Universitas Muhammadiyah Sumatera Utara, 2022)
Background: Lipids come in from many different sources in ones diet. In this experiment, we intend to find out the kind of lipids that causes the highest increase in rat body weight and the most influence in the lipid profiles. Method: We compared three kinds of lipid: beef fats, egg yolk and palm oil which were added to the rats standard diet. Twenty-eight 20-24 week-old male Sprague-Dawley rats weighing 250300 g were randomly divided into 4 treatment groups given a high beef fat diet (BF), a high egg yolk (EY), a high vegetable fat (VF), and a standard chow diet (SD) as control for 30 days. The body weight of each rat was monitored weekly and the lipid profiles were measured enzymatically at the end of the experiment. Result: The EY and VF body weights increased significantly compared to the SD (p0.05). The total cholesterol level of BF, EY and VF increased significantly compared to the SD groups (p0.001). The triglycerides level of BF, EY, and VF increased significantly compared to SD (p0.001). The HDL-cholesterol levels were significantly lower in BF, EY and VF compared to SD (p0.05). The LDL-cholesterol in BF, EY and VF were significantly increased compared to SD (p0.05). Conclusion: High egg yolk diet causes a bigger increase in rat body weight, LDL levels, cholesterol levels, and triglycerides than the high beef fat diet and high vegetable fat diet compared to control. It also causes lower HDL levels than the other diet groups compared to control.